Panini’s Grammar in Computer Science - Saxena2, Parul Saxena1*, Kuldeep Pandey2, Vinay (Recent Research in Science and Technology, 2011)
In the present work, we have described the contribution of the Great Indian mathematician Panini to the Modern Computer Science, it is the most appropriate approach of us to make the reader familiar with the great history of the Indian mathematics and modern applications of those. This will lead to new inventions and searches of the Indian mathematician to link with the modern world, which is the key aim of us.